DESIGN OF SAFETY FACTORS FOR LANDSLIDE POTENTIAL AND ANDESITE MATERIAL SLOPES GEOMETRY - Haryono, Ahmad Fauzan; Razak, Supardi; Kusumaningsih, Dewi Ayu (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2024)
This research was conducted because the material absorption capacity needs to be maximized, so it is necessary to make a mining slope geometry with an optimal safety factor value so that there is no potential for landslides in the research area. The method used is the morgenstern price method, this method was chosen because it has considered the stability of moments and forces.The actual slope geometry that has not been tested for safety needs to be changed. The physical and mechanical properties data collection is processed to produce a geometric model with a safety factor in accordance with applicable regulations. The actual slope geometry of the Cijurey block is 20m with a slope of 85o, 8m with a slope of 88o, 5m with a slope of 83o and 4m with a slope of 85o with a safety factor value of 1.01. A geometric change was made with a slope height of 6 m and a ladder width of 3m which was made multi-level with an overall angle of 80o having a safety factor of 1.302 which means that it has met the slope safety criteria.Keywords: safety factor, geometry, slope